Charleston and Christchurch and the Politics of Postracial Forgiveness. (6th May 2022) - Ghumkhor, Sahar
Abstract : This article explores the political work of forgiveness in a secular liberal West by examining the aftermath of two white supremacist violent events: the Charleston church attack in 2015 and the Christchurch mosque attacks in 2019. The article examines how the exaltation of forgiveness over anger after such events is symptomatic of what David Theo Goldberg (2015) calls the "postracial" turn which denies the structural harm of racism and privileges social unity at a time when racism bears its most violent face. What can be ascertained in centring forgiveness, and therefore the unifying figure of the victim of white supremacist violence, is how the postracial conceals the persistence of race as the secular investment and regulation in the articulation of religion in public life.